Zirconyl Hydrogenphosphate Nanocontainers for Flexible Transport and Release of Lipophilic Cytostatics, Insecticides, and Antibiotics. (22nd May 2019) - Rein, Viktor; Meschkov, Anna; Hagens, Kristine; Redinger, Natalja; Schepers, Ute; Mehlhorn, Heinz; Schaible, Ulrich E.; Feldmann, Claus
Abstract: Administration of lipophilic drugs is often restricted by poor aqueous solubility (especially in blood), limited membrane permeability, uncontrolled drug leakage, and aggregation of lipophilic drugs. As a new nanocarrier concept, LC@ZrO(mdp)@ZrO(HPO4 ) core@shell nanocontainers (LC: lipophilic cavity; mdp: monododecylphosphate) are presented. As a proof of concept, the nanocontainers are used to encapsulate different types of lipophilic molecules such as the fluorescent dye lumogen red (LR), the cytostatic drug irinotecan (ITC), the insecticide cypermethrin (CM), and the tuberculosis antibiotic benzothiazinone‐043 (BTZ). Synthesis strategy and material structure of the nanocontainers are discussed in detail. LR@ZrO(mdp)@ZrO(HPO4 ), as the first example, shows intense red emission and successful incorporation of LR into the nanocontainers. As ex vivo application, CM@ZrO(mdp)@ZrO(HPO4 ) nanocontainers can be used to repel and even kill mosquitoes or flies being in contact with the insecticide‐loaded nanocontainers. The drugs ITC and BTZ—after encapsulation in ITC@ZrO(mdp)@ZrO(HPO4 ) and BTZ@ZrO(mdp)@ZrO(HPO4 ) nanocontainers—show high activity at low cytotoxicity in in vitro studies against tumor cells (HeLa, SK‐Mel‐28, HTC116, A549, RAW264.7) and tuberculosis ( Mycobacterium tuberculosis ‐infected macrophages). Taken together, the different lipophilic molecules (LR, CM, ITC, BTZ) point to the adaptability and performance of the novel zirconyl hydrogenphosphate nanocontainer concept. Abstract : LC@ZrO(mdp)@ZrO(HPO4 ) core@shell nanocontainers (LC: lipophilic cavity) are suggested as a novel nanocarrier concept for lipophilic molecules. Feasibility and adaptability are exemplarily presented for the fluorescent dye lumogen red, the cytostatic drug irinotecan, the insecticide cypermethrin, and the tuberculosis antibiotic benzothiazinone‐043.